Technology revolution 4.0 is a social-economic development solution for developing countries (Revista de Investigaciones Universidad del Quindío, 2023)
Facing the inevitable development trend of the economy and the challenges posed by the requirements of building a digital economy, developing countries need to develop the country's socio-economic development. The technology revolution has pushed countries’ economies to grow in the direction of linking global economies. As a result, developing countries face many challenges in maintaining strong macroeconomics, controlling external debt and inflation, and investing effectively in infrastructure and technology capabilities that will contribute to productivity growth. The article uses analysis, comparison, and synthesis methods to clarify the role of the technological revolution on the economies of developed countries in controlling the macroeconomic environment and allocating resources. The article also describes the reality of the application of 4.0 technology in Vietnam to clarify other countries' transition from low-income to high-income status through technology application.
Keywords: 4.0 technology revolution; economy - society; developing country